2019
DOI: 10.1200/jco.2019.37.15_suppl.e12009
|View full text |Cite
|
Sign up to set email alerts
|

Decisions on adjuvant chemotherapy for patients with breast cancer based on clinical and evolving Oncotype DX criteria.

Abstract: e12009 Background: Oncotype-DX assay recurrence score (ODX-RS) cut-off values have recently changed in response to the results of the TAILOR-X trial. We aim to explore decisions for ACT based on physicians’ clinical assessment and on evolving ODX-RS. Methods: Patients who underwent ODX testing after curative surgical resection of estrogen receptor positive (ER+), Her2 non-over-expressed (Her2-) and lymph node negative (LN-) BC were included. Patients with micro-metastases to LNs were excluded. Data was collec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 0 publications
1
3
0
Order By: Relevance
“…Although a new classification has been proposed by the TAILORx data (low: < 11, intermediate: 11-25, and high: > 25) [ 10 ]. Our study applied the traditional classification which is supported by the observation of Zekri et al that found no statistically significant difference in prescribing AC by three blinded oncologists using the two classifications [ 21 ]. Controversy and challenge in the management of patients with intermediate RS of 11 to 17 exist when applying the updated classification.…”
Section: Discussionsupporting
confidence: 60%
See 3 more Smart Citations
“…Although a new classification has been proposed by the TAILORx data (low: < 11, intermediate: 11-25, and high: > 25) [ 10 ]. Our study applied the traditional classification which is supported by the observation of Zekri et al that found no statistically significant difference in prescribing AC by three blinded oncologists using the two classifications [ 21 ]. Controversy and challenge in the management of patients with intermediate RS of 11 to 17 exist when applying the updated classification.…”
Section: Discussionsupporting
confidence: 60%
“…The mean ODx recurrence score of our cohort was 17.8 ± 8.6. Categorical distribution of the RS revealed 79 cases (54.5%) had low-risk (0-17), 55 (37.9%) had intermediate-risk (18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30), and only 11 (7.6%) had high-risk (31-100). The progesterone receptor was positive in 139 cases (95.9%) and negative in only six cases (4.1%).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations